FRI0548 Responsiveness of A New MRI Scoring Method Based on The Canada-Denmark Definitions of Lesions in The Spine and The SPARCC MRI Spine Inflammation Index in Patients with Axial Spondyloarthritis. (15th July 2016) - Krabbe, S.; Østergaard, M.; Sørensen, I.J.; Jensen, B.; Møller, J.; Balding, L.; Madsen, O.R.; Asmussen, K.H.; Eng, G.P.; Pedersen, S.J.
Abstract : Background: The Spondyloarthritis Research Consortium of Canada (SPARCC) Spine Inflammation Index is a well-established MRI scoring system for vertebral body inflammation.(1) It does not take the exact anatomical location of lesions into account. The Canada-Denmark (CanDen) MRI definitions were developed to allow detailed anatomical evaluation of inflammatory and structural lesions of the vertebral bodies as well as the posterior segments in patients with axial spondyloarthritis (axSpA).(2–3) Objectives: The aim of this study was to assess the distribution of scores and the responsiveness of this new method, which combines the CanDen MRI definitions into a scoring system, as compared with the SPARCC Spine Inflammation Index in an axSpA randomized controlled trial. Methods: For each disco-vertebral unit, inflammatory lesions of vertebral bodies (VB) in the anterior and posterior corners on central sagittal slices were scored as 1 (small) or 2 (large). Non-corner lesions were scored as 2 (small) or 4 (large). Antero-lateral and postero-lateral inflammatory corner lesions in lateral sagittal slices were scored as 1. Inflammatory lesions in the posterior segments (PS) were each scored as 1. Fat (4), erosion and new bone formation were scored in a comparable way (details not shown due to length restrictions). 49 patients with axSpA and indication for TNFα inhibitor were randomized to placebo or adalimumab 40 mg sc. eow for 6 weeks. MRI of the spine was scored according to CanDen definitions and SPARCC by an experienced reader blinded to the clinical data. Responsiveness was assessed by standardized response mean (SRM) and Guyatt's responsiveness index (GRI). Values ≥0.8 represent a large degree of responsiveness. Results: Conclusions: A new anatomy-based scoring system for spine inflammatory and structural lesions was described, demonstrating similar responsiveness as the SPARCC method. Further studies are needed to investigate the additional value of assessing posterior segments. References: Maksymowych et al. Arthritis Rheum 2005;53:502–9; Lambert et al. J Rheumatol 2009;36-S84:3–17; Østergaard et al. J Rheumatol 2009;36-S84:18–34; Pedersen et al. Arthritis Res Ther 2013;15:R216 Disclosure of Interest: None declared